28. Speak2Me: Using Synchronous Audio for ESL Teaching in Taiwan - LaPointe, Deborah K.; Greysen, Katherine R. B.; Barrett, Kerrin A. (International Review of Research in Open and Distributed Learning, 2004)
The use of a synchronous audio tool is discussed for teaching English as a Second Language (ESL) in Taiwan. Over several months, a community of practice has formed among teachers and teaching assistants, transcending cultural differences. Exploring the relationship that has developed between teachers and teaching assistants forms the basis of this report. We will also consider the technology underlying Speak2Me's program and its relationship to providing students with quality pedagogy and learning flexibility.